The Federal Home Loan Bank Board - Marvell, Thomas B. (New York : Praeger, 1969)
The book examines the performance of the Federal Home Loan Bank Board service to the industry and the profound effects of tight-money problems in United States. In addition, discussions of the Federal Home Loan Bank Board's attempts to deal with wayward savings and loan associations and the continuous interplay among the agency, Congress, the savings and loan industry.
Includes index.
Includes bibliographical references: p. 281-282.
usc 21/09/2017
Loans
Keywords: Federal Home Loan Bank Board; United States